Mathematics Achievement vs Parenting Style - Reni Untarti; Anggun Badu Kusuma (International Journal of Advanced Science and Technology, 2020)
The students’ characteristics determine the achievement to master mathematics, and the parenting style determines the students’ character building. This research described the parenting style, which was related to the students’ mathematics achievement. This research belongs to descriptive qualitative research using 76 students of first-year mathematics education as the subject of the study. The data were obtained from the questionnaire, documentation, observation, and in-depth interview. The research shows that the authoritative parenting style is the best style related to mathematics learning achievement. Besides, the authoritarian, although it can’t be better comparing with authoritative, can develop the mathematics learning achievements as well. Permissive style is considered not to develop the students to get the achievement in mathematics and also the rejecting-neglecting style too. However, the best achievement in mathematics is achieved by students with permissive parenting.